Trends in Elementary School Statistical Literacy Research: A Bibliometric Analysis - Alman; Prabawanto, Sufyani; Herman, Tatang (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
Statistical literacy is an essential skill that is increasingly important in the information age, where the ability to understand, analyze, and interpret statistical data is an integral part of primary to secondary education. Amid technological developments and increasingly widespread access to data, statistical literacy is key in helping individuals make decisions based on strong evidence. This research aims to determine the research development on elementary school statistical literacy. The method used in this research is the bibliometric analysis method. The results of computational mapping, and interpreting the findings from the search results, obtained 200 articles from search results on Google Scholar using Publish or Perish that were relevant to elementary school statistical literacy from 2014 to 2024. The research results show that research on elementary school statistical literacy is minimal. From article analysis using VOSviewer, the development of publications related to statistical literacy from 2014 to 2024, out of 200 publications pertaining to statistical literacy, there are 6 publications. From these results, it can be concluded that studies on elementary school statistical literacy research are still limited. This means that research on this topic has a great opportunity to be carried out in the future to provide novelty in research.